INDICATORS WHICH MEASURE A LEVEL OF SIGNIFICANCE OF AGRICULTURE IN SERBIA - Jonel SUBIĆ; Biljana GRUJIĆ; Marijana JOKSIMOVIĆ (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Although agriculture is a significant activity for every country, many are frightened out of being engaged in this activity, due to insufficient importance given to it. This paper will show three indicators, by which can be measured the significance of agriculture for a certain country, and these are: the share of rural population in total population, the share of employed population in agriculture in total number of employees and the share of agriculture in creating a gross domestic product (GDP). It’s also an important indicator of agricultural share in foreign trade exchange. The obtained data will be shown for the period 2012-2015 and commented in accordance with the obtained values. Processed results did provide the following results (the change index 2015/2012): the share of rural population in total population was decreased for 2.5 percentage points (p.p.), the share of population employed in agriculture in total number of employed population was decreased for 2 p.p., while a chain index of GDP share in agriculture is at extremely low level and in the year 2015, in regard to the year 2014, was lower for 7.5 p.p. Declining values of indicators only point out to a low level of significance of agriculture for Serbia, which is characterized by favourable natural factors for farming. An indicator „the share of agriculture, forestry and fishery in total export of Serbia“ is the only one which records the increasing values in the period 2013-2015 for 1.2 p.p., but in regard to the initial year 2012, is yet lower for 1.5 p.p. The conclusion is drawn, by using the mathematicalstatistical methods and research methods, that agricultural activity for Serbia is not sufficiently important.